(untitled) (Journal of the Sociology and Theory of Religion, 2018)
The author starts from the following approach: religion (in general, not identified with any particular confession), is a type of knowledge, with its concepts and theories, such as science, or philosophy. It is also a vigorous social sphere, with its norms and institutions, such as politics and law. Even, it can be understood as a factor of transformation and / or social stagnation, through movements and campaigns, affecting the evolution of communities.